Abemaciclib and Letrozole in Metastatic Male Breast Cancer - Leon Schönfeld; Christian Möhring; Rouven Strobel; Hanns Leonhard Kaatsch; Stephan Waldeck; Ulrike Wagner (Cancer Reports)
ABSTRACT Background Male breast cancer is a very rare disease and only accounts for around 1% of all breast cancers. The treatment strategies are based on those used for breast cancer in women. So far, there is a lack of randomized data to support specific treatment modalities in men. To our knowledge, a therapeutic approach with a combination of letrozole and abemaciclib has not yet been described for a male patient with metastatic breast cancer. Case Description Here, we report a case of a male patient with advanced metastatic breast cancer treated with a combination of letrozole and abemaciclib. The therapy was well tolerated with no reported side effects. The follow‐up CT showed regression of the primary tumor mass and the lymph nodes and soft tissue metastases. Conclusion In summary, this case report clearly shows the effectiveness of the therapeutic approach and should be discussed for the treatment of future patients.